IMPLEMENTATION OF WI-FI BASED INTERNET NETWORK CONNECTION AND INTRODUCTION TO TEACHERS AND STUDENTS OF STATE SENIOR HIGH SCHOOL 1 DOLOK SANGGUL - Adriwanto (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
Wireless communication has become a basic need or a new lifestyle for people in obtaining information, especially in the SMA Negeri 1 Dolok Sanggul environment. In this community service, the PKM activity implementation team was given the opportunity to build a wireless network using a Mikrotik RB951. This was done to empower the densely populated SMA Negeri 1 Dolok Sanggul environment which has the potential to be used as a hotspot business. The method used was a direct practice method for students by implementing health protocols during the pandemic. In addition, a wireless-based network makes it easier for students to access the internet anywhere. The implementation of the network installation consists of several units of RJ-45 connectors on UTP cables, access point configuration, and Mikrotik hotspot server configuration. With the presence of a wireless network in the SMA Negeri 1 Dolok Sanggul environment, it will make it easier for students and teachers to access the internet. In addition, configuring a wireless network is not that difficult, as long as you follow the rules for creating a network.